Analysis of Long-Term Meteorological Observation for Weather and Climate Fundamental Data over the Northern Tibetan Plateau. (24th December 2015) - Huang, Fangfang; Ma, Weiqiang
Abstract : Meteorological observation plays a critical role in climatic study, and in situ measurements are the foundation of meteorological observation, especially in the Tibetan Plateau, the surface of which is fairly complex. Several field stations in the Northern Tibetan Plateau, which features relatively homogeneous surface, were selected as the study area. A detailed description on the significance of site observation for climate prediction was given in this paper. Data from weather stations can be used to verify satellite data and provide parameters for initial mode field in the study of weather and climate changes. The field observation data in the Northern Tibetan Plateau from 2001 to 2013 is analyzed. The results show that in El Nino year, values of land surface temperature (T s ), air temperature (T a ) and wind speed are all greater than their mean values and that soil moisture values are lower than the averaged, while the opposite is the case in La Nina year. The warming rate in the Northern Tibetan Plateau is greater than that in global areas. The diurnal variations ofT s andT a are various in different seasons and underlying surfaces, with the diurnal variations greater in spring, and less in summer and autumn. Furthermore, the diurnal variation in the area with drier underlying surface is more obvious than that in area with moist surface.